Analysis of Driving and Inhibiting Factors in Used Cooking Oil Management Based on Social and Environmental Responsibility in Catering Businesses - Siti Mahsanah Budijati; Muhammad Hijrah Tanjung; Isaac John Ibanga (Engineering Science Letter, 2025)
The improper disposal of used cooking oil (UCO) poses significant environmental and health risks, particularly when not managed responsibly by food-related businesses. This study aims to identify and analyze the most influential driving and inhibiting factors affecting UCO management in catering businesses, with a particular focus on social and environmental responsibility. The research adopts the Analytic Hierarchy Process (AHP) to systematically assess the priority levels of multiple criteria across 15 catering companies. AHP was chosen due to its strength in structuring complex decision-making problems through pairwise comparisons and eigenvalue analysis. Data were collected using both quantitative questionnaires and qualitative open-ended responses, allowing for a comprehensive understanding of stakeholder perspectives. The results show that among the driving factors, the most dominant is internal policy or management commitment, followed by factors such as enhancing company reputation and increasing profit. Conversely, the top inhibiting factor is the lack of knowledge related to proper oil waste handling, with other significant barriers including high processing costs and insufficient infrastructure. These findings emphasize that managerial awareness, education, and access to resources are crucial for advancing sustainable practices. The study suggests that enhancing knowledge and reinforcing managerial commitment are key strategies to improve oil waste management practices in the catering industry.